2022
DOI: 10.1093/eurjpc/zwac277
|View full text |Cite|
|
Sign up to set email alerts
|

Persistence with long-term PCSK9 inhibitor treatment and its effectiveness in familial hypercholesterolaemia: data from the SAFEHEART study

Abstract: Aims Most heterozygous familial hypercholesterolemia (FH) patients require intensive lipid-lowering therapy (LLT) including PCSK9 inhibitors (PCSK9i) to reach current LDL-C goals. Persistence with chronic treatment is important to reduce the burden of atherosclerotic cardiovascular disease. We analysed persistence, efficacy, and impact on quality of life of PCSK9i in FH patients in clinical practice setting. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It was reported that long-term persistent lipid-lowering therapy with a PCSK9 inhibitor had reduced the burden of atherosclerotic cardiovascular disease to achieve LDL-c goals in high-risk FH patients with ACS in a clinical practice setting [ 7 ]. Few FH patients received intensive combined lipid-lowering treatment containing a PCSK9 inhibitor in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that long-term persistent lipid-lowering therapy with a PCSK9 inhibitor had reduced the burden of atherosclerotic cardiovascular disease to achieve LDL-c goals in high-risk FH patients with ACS in a clinical practice setting [ 7 ]. Few FH patients received intensive combined lipid-lowering treatment containing a PCSK9 inhibitor in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to accurately diagnose and screen FH in patients with ACS. Long-term lipid-lowering therapy can reduce the burden of atherosclerotic cardiovascular disease in high-risk FH patients with ACS [ 7 10 ], but few FH patients can achieve the target LDL-c level of < 1.8 mmol/L and a reduction > 50% from baseline. In addition, FH is an independent risk factor for major adverse cardiovascular and cerebrovascular events (MACCE) in patients after a coronary event during long-term follow-up [ 8 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also demonstrated low rates of LDL-cholesterol goal attainment in FH [19,20,21 ▪ ]. Likewise, more than 50% of FH patients fail to attain recommended LDL-cholesterol goals even when additionally treated with PCSK9 inhibitors [22 ▪ ]. Poor patient adherence to LLT is the major contributor to the lack of LDL-cholesterol goal attainment [2 ▪▪ ,8 ▪ ].…”
Section: Lipid-lowering Treatment: Benefits and Goals In Familial Hyp...mentioning
confidence: 99%
“…Likewise, nonadherence to PCSK9 inhibitors or treatment discontinuation were reported in 20–30% of high-risk patients [31–34]. However, a recent report from the SAFEHEART study showed a high persistence with long-term PCSK9 inhibitor treatment, with only 4% of FH patients discontinuing treatment after a median follow up of 3.7 years [22 ▪ ]. As discussed later, discrepant findings on nonadherence to PCSK9 inhibitors may be reflected by differences in patient and healthcare system related factors that bear on out-of-pocket medication costs.…”
Section: Adherence To Lipid-lowering Treatmentmentioning
confidence: 99%